2010
DOI: 10.4103/0973-1296.71785
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents from Alpinia purpurata and their in vitro inhibitory activity against Mycobacterium tuberculosis

Abstract: Alpinia purpurata or red ginger was studied for its phytochemical constituents as part of our growing interest on Philippine Zingiberaceae plants that may exhibit antimycobacterial activity. The hexane and dichloromethane subextracts of the leaves were fractionated and purified using silica gel chromatography to afford a mixture of C28–C32 fatty alcohols, a 3-methoxyflavone and two steroidal glycosides. The two latter metabolites were spectroscopically identified as kumatakenin (1), sitosteryl-3-O-6-palmitoyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Compound (1) has been isolated previously from A. flabellata, 9 while compound (2) from Alpinia purpurata. 10 Besides, compounds (3) and ( 4) have been isolated previously from Zingiber cassumunar, 11 while compound (5) from A. flabellata. 12 In addition, compounds (6) and ( 7) have been reported previously from A. globosa.…”
Section: Resultsmentioning
confidence: 99%
“…Compound (1) has been isolated previously from A. flabellata, 9 while compound (2) from Alpinia purpurata. 10 Besides, compounds (3) and ( 4) have been isolated previously from Zingiber cassumunar, 11 while compound (5) from A. flabellata. 12 In addition, compounds (6) and ( 7) have been reported previously from A. globosa.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of ferroptosis proved to be an attractive approach for treatment of IBD. Kumatakenin is a polymethoxylated flavonoid isolated from traditional Chinese medicinal cloves and Alpinia purpurata (Villaflores et al, 2010;Woo et al, 2017). Previous work has Frontiers in Pharmacology frontiersin.org confirmed that kumatakenin exerts significant anti-inflammatory effects, and induced cell death of cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Kumatakenin also inhibits SARS-CoV-2 replication in Vero E6 and Calu-3 cells (Leal et al, 2021). Finally, kumatakenin has been shown to suppress cytokine production (Villaflores et al, 2010). However, the influence of kumatakenin on IBD remains unclear.…”
Section: Open Access Edited Bymentioning
confidence: 99%
“…The column chromatrography of the ethyl acetate extract of M. glabra resulted in the isolation of quercetin 3, 5, 3'-trimethyl ether (1) [20] and kumatakenin (2) [21]. The isolation of the methanol extract of M. glabra afforded scoparone (3) [22], 6, 7, 8-trimethoxycoumarin (4) [23], marmesin (5) [24], glabranin (6) [13], umbelliferone (7) [25], scopoletin (8) [26] and sesamin ( 9) [27].…”
Section: Isolation Of Compounds From M Glabra Extractsmentioning
confidence: 99%